Irradiation Effect on F321 Austenitic Stainless-Steel: Nanoindentation and Modeling With the Crystal Plasticity Method - Liu, Meidan; Nie, Junfeng; Lin, Pandong (Frontiers in Materials, 2022)
In this study, 3.5 MeV Fe-ion irradiation experiments were conducted on F321 austenitic stainless-steel at different temperatures and doses. The nanohardness of the unirradiated and irradiated samples was characterized by performing nanoindentation experiments. Irradiation softening and hardening were clearly observed at 20, 100, and 300°C. However, at 300°C, after irradiation softening, the nanohardness first increased and then decreased, as opposed to the nanohardness at 20 and 100°C, which increased as the dose increased. In addition, a crystal plasticity model for a face-centered cubic single-crystal while considering irradiation-induced hardening has been proposed and numerically implemented in the user-material subroutine UMAT of ABAQUS. This was done to simulate the load-depth data of the nanoindentation experiment. The simulated results of the non-irradiated and irradiated F321 austenitic stainless-steel were compared with the experimental data. A good agreement was observed, which demonstrates the effectiveness and accuracy of the model.